1991
DOI: 10.1007/bf02599381
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the efficacy of physician-delivered smoking interventions

Abstract: Smoking intervention counseling provided by physicians is well received by patients and significantly increases the likelihood of cessation at six months, an effect that is augmented by the prescription of nicotine-containing gum, when compared with physician-delivered advice. Follow-up telephone counseling does not contribute significantly to smoking behavior changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
0
4

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 239 publications
(94 citation statements)
references
References 25 publications
7
83
0
4
Order By: Relevance
“…We believe the results of this study are applicable to any multiphysician office practice in which patient volume is high and there is a mix of HMO and fee-for-service patients. Although this article describes an alcohol-counseling intervention, we have demonstrated similar outcomes with smoking, 28 and dietary behavior. 18 It also is likely that our findings would apply to other brief, provider-delivered office interventions such as for exercise.…”
Section: Discussionmentioning
confidence: 75%
“…We believe the results of this study are applicable to any multiphysician office practice in which patient volume is high and there is a mix of HMO and fee-for-service patients. Although this article describes an alcohol-counseling intervention, we have demonstrated similar outcomes with smoking, 28 and dietary behavior. 18 It also is likely that our findings would apply to other brief, provider-delivered office interventions such as for exercise.…”
Section: Discussionmentioning
confidence: 75%
“…This method has been associated with significantly more change in dietary behavior, 18 smoking behavior, 19 and reduced high-risk drinking at 6-month follow-up when compared to usual primary care. 20 Project Health is a controlled clinical trial that compares a special intervention (SI) consisting of patient-centered counseling for high-risk drinkers to usual care (UC) in the primary care setting.…”
mentioning
confidence: 96%
“…Our past research has demonstrated that screening, brief provider-delivered patient-centered counseling, and prompting providers to intervene has a significant effect on change in health-related behaviors 18,19 when used in the primary care setting during regular primary care visits. This method has been associated with significantly more change in dietary behavior, 18 smoking behavior, 19 and reduced high-risk drinking at 6-month follow-up when compared to usual primary care.…”
mentioning
confidence: 99%
“…We estimated the quit responses based on the expected quit responses reported in the literature for the various levels of service and on the previous results reported by the services for level 1 (enrollment and Quit Line use with usual quit rate of 25%), level 2 (brief intake and information only with usual quit rate of 15%), and level 0 (no intake and clinician advice alone with usual quit rate of 10%). 7,11,29,[31][32][33] Measures and Outcomes Key measures and outcomes included (1) changes from baseline to postintervention (18 months) in clinician referrals in both intervention and control groups, (2) estimated quit responses of referred smokers, and (3) estimated incremental costs of the feedback intervention. …”
mentioning
confidence: 99%